2020
DOI: 10.1093/aobpla/plaa041
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis in osmo-primed tomato seeds with enhanced longevity by heat shock treatment

Abstract: Seed priming is widely used in commercial seeds and its main function is to accelerate and synchronize seed germination. Undesirably, primed seeds show reduced longevity and treatments like heat shock have been shown to improve longevity in primed seeds. Nonetheless, the effect of heat shock treatment on primed seeds at the mRNA level is not known. Thus, the aim of this work was to investigate the effect of heat shock treatment on the longevity of primed tomato (Solanum lycopersicum) seeds at the physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…According to Brandão and Lopes (2019), this test can generate inaccurate results in small-sized seeds, as in the case of pepper seeds.The beneficial effect of seed conditioning may not persist over the seed storage period (Batista et al, 2020;Silva and Marcos -Filho, 2020). According to Marcos Filho (2015), the process has several advantages, as the physiological conditioning guarantees the absorption of water under controlled conditions, allowing the beginning of the germination process, activating phases I and II of germination, but not the phase of radicle protrusion.…”
Section: Resultsmentioning
confidence: 99%
“…According to Brandão and Lopes (2019), this test can generate inaccurate results in small-sized seeds, as in the case of pepper seeds.The beneficial effect of seed conditioning may not persist over the seed storage period (Batista et al, 2020;Silva and Marcos -Filho, 2020). According to Marcos Filho (2015), the process has several advantages, as the physiological conditioning guarantees the absorption of water under controlled conditions, allowing the beginning of the germination process, activating phases I and II of germination, but not the phase of radicle protrusion.…”
Section: Resultsmentioning
confidence: 99%
“…An element of the germination vigour conferred by priming may also result from stresses incurred during the priming process. For example, tomato seed priming was improved by heat shock, which also led to elevated heat shock factor gene expression [ 140 ]. Priming alters ROS levels, with reduction in hydrogen peroxide accumulated in aged seeds, accompanied by increased catalase activity as seeds recover from the loss of catalase protein during ageing [ 135 , 137 , 141 ].…”
Section: Mitigating the Effects Of Desiccation And Quiescence On Seed...mentioning
confidence: 99%
“…This can be ameliorated by heat shock to primed seeds. The genetic determinants of this improvement in longevity were investigated using primed and dried tomato seeds [ 154 ]. RNA-seq and subsequent transcriptome analysis of the tomato seeds after priming and after heat shock treatment post-priming demonstrated that from a total of 368 differentially expressed genes, 298 genes were up-regulated and 70 were down-regulated.…”
Section: Genetic Studies In the 21st Centurymentioning
confidence: 99%